Pedagogy of Change according to André Giordan - Potyrała, Katarzyna (Educational Research E-Books Online, Collection 2026., 2025)
"Changing pedagogy" changes everything. The adoption and implementation of the modified pedagogy begins with critical reflections related to teaching and learning, and the implementation of the pedagogy of change begins with personal experience and the need to change the world in the micro-, meso-, and macro-dimensions. The idea of this book is to show how a man's destiny is closely linked to his activity. This is proven by a biographical analysis of André Giordan's course of life in the heterocentric aspect, because - as Charlotte Bühler argues - it makes it possible to trace the main ideas and products of the researcher's thought when the individual in his expansion is replaced by the expansion of his own productions. In analyzing André Giordan's social and scientific activity, it is impossible to ignore the dynamics of creative passion, especially in the context of the influence of the social environment on the development of the individual. The positive multi-layered and multifaceted disintegration (according to Kazimierz Dąbrowski's theory) fostered creative development. The different "levels" of this development are responsible for the formation of experience and find expression in the structure of work and in the various forms of expression.